Morphological plasticity of ectomycorrhizal short roots in Betula sp and Picea abies forests across climate and forest succession gradients: its role in changing environments - Ostonen, Ivika; Rosenvald, Katrin; Helmisaari, Heljä-Sisko; Godbold, Douglas; Parts, Kaarin; Uri, Veiko; Lõhmus, Krista (Frontiers in Plant Science, 2013)
Morphological plasticity of ectomycorrhizal (EcM) short roots (known also as first and second order roots with primary development) allows trees to adjust their water and nutrient uptake to local environmental conditions. The morphological traits of short-living EcM roots, such as specific root length (SRL) and area, root tip frequency per mass unit (RTF), root tissue density, as well as mean diameter, length, and mass of the root tips, are good indicators of acclimation. We investigated the role of EcM root morphological plasticity across the climate gradient (48°N–68°N) in Norway spruce (Picea abies (L.) Karst) and (53°N -66°N) birch (Betula pendula Roth., B. pubescens Ehrh.) forests, as well as in primary and secondary successional birch forests assuming higher plasticity of a respective root trait to reflect higher relevance of that characteristic in acclimation process. We hypothesized that although the morphological plasticity of EcM roots is subject to the abiotic and biotic environmental conditions in the changing climate, the tools to achieve the appropriate morphological acclimation are tree species-specific. Long-term (1994-2010) measurements of EcM roots morphology strongly imply that tree species have different acclimation-indicative root traits in response to changing environments. Birch EcM roots acclimated along latitude by changing mostly SRL (plasticity index (PI) =0.60), while spruce EcM roots became adjusted by modifying RTF (PI=0.68). Silver birch as a pioneer species must have a broader tolerance to environmental conditions across various environments; however, the mean plasticity index of all morphological traits did not differ between early-successional birch and late-successional spruce. The differences between species in SRL, and RTF, diameter, and length decreased southward, towards temperate forests with more favourable growth conditions. EcM root traits reflected root-rhizosphere succession across forest succession stages.